The reeve's tale - Frazer, Margaret, 1946-2013 (Thordike Press, 2000)
A PLAGUE OF MURDERSThe village of Prior Byfield is blighted with famine, devastated by plague, and cursed with ill-fortune. Simon Perryn, the poor reeve of the village, is driven to distraction by the petty rivalries and hopeless troubles of his neighbors. His adulterous sister and her dolt of a husband have entangled their affairs with Gilbey Dunn, the richest man of the village, and Elena, the beautiful and seductive woman that he calls his wife. With wealth on the line and lives at the stake, old quarrels and ancient angers are boiling over into the once-quiet streets of the village. That's when things get even worse for Simon: A horrid scandal curses him with a pair of nuns, sent from the nearby nunnery of St. Frideswide's to make sure all is kept right in the village.Dame Frevisse, however, suspects that the scandal which has drawn her and the innocent Sister Thomasine from the safety of the priory is but the tip of a terrible intrigue which threatens both nunnery and village alike: The good, kind, and honest Master Naylor stands accused of a crime which threatens to strip him and his entire family of their freedom. Who could stand to profit from his loss? Is it the same silent killer who stalks the village youth? Or are they all being played like fools?Yet even if Frevisse's keen wit can lay bare the ugliness in the hearts of men, she fears that no amount of prayer will serve to cleanse her own soul of that sickly hate. Can even God pardon one who has turned from a holy path?PRAISE FOR THE REEVE'S TALE"Everything about it bespeaks quality and care... Frazer draws us into a medieval village in England with a story of lust, greed and murder." - St. Paul Pioneer Press"Exquisitely written, the novel offers a brilliantly realized vision of a typical medieval English village, peopled with full-blooded men and women who experience the human range of joys and sorrows. Suspenseful from start to surprising conclusion, this is another gem from an author who's twice been nominated for an Edgar." - Publisher's Weekly"This tale is a trip back in time, a time when your personal wants had to be satisfied with what could be found in your immediate surroundings. You will appreciate the intense need for each village and villager to be self-sufficient. You experience the terror caused when children fall ill. The Reeve's Tale is a fascinating one." - Martha's Vineyard Times"Frazer [turns] the screw of the mystery... The looming threats guarantee suspense... Greed and self-interest lurk beneath marital agreements knotted to land contracts, reminding God's virgins just who feeds them." - Kirkus ReviewPRAISE FOR THE DAME FREVISSE MEDIEVAL MYSTERY SERIES"Within the graceful prose rhythms that have garnered her two Edgar nominations, Frazer's 10th tale of 15th-century nun Dame Frevisse transports the reader to a medieval England made vivid and a world of emotions as familiar then as now." - Publisher's Weekly"Frazer's quiet yet intense medieval mysteries are so vividly and gracefully written you just float back in time..." - The Poisoned Pen"Those who meet Frevisse here for the first time will want to get to know more about more." - Detroit Free Press"Ms. Frazer provides a real treat for lovers of all things medieval." - Romantic Times"Frazer is a master because she combines her love and knowledge of history with the true skills of a mystery writer." - Aunt Agatha'sA Romantic Times Top Pick.Twice nominated for the Minnesota Book Award.Twice nominated for the Edgar Award.